Identification of Traits Contributing to High and Stable Yields in Different Soybean Varieties Across Three Chinese Latitudes - Li, Minmin; Liu, Ying; Wang, Chunsheng; Yang, Xue; Li, Dongmei; Zhang, Xiaoming; Xu, Chongjing; Zhang, Yan; Li, Wenbin; Zhao, Lin (Frontiers in Plant Science, 2020)
Soybean yield was a complex quantitative trait, which was greatly affected by environmental conditions. The main objective of this study was to analyze genotype x environment (G x E) interaction on the grain yield and its components to identify the soybean varieties with stable and the highest yield across different environments. One hundred and seventy-three soybean genotypes were tested in three different ecological environments in China during 2015-2016 cropping seasons. The evaluation on the different agronomic and physiological traits indicated that the soybean varieties with higher plant height, more nodes of main stem, branches, pods, grains and 100-grain weight, or longer growth periods may have higher yield. Pods, grains and 100-grain weight can be used as direct selection criteria for yield increase, and likewise the other traits such as plant height, nodes of main stem, branches, pods, grains, 100-grain weight, growth periods indirectly affected yield by affecting the three traits above. The combined effects of genotype, environment and G x E interaction determine the yield of the crop. The representativeness and discriminability for grains yield per plant was the most significant in Harbin, which could be used to screen varieties with high-yield and wider adaptability. Genotype ‘Suinong 1’ was considered stable with the highest phenotypic value of grain yield per plant. The evaluation of stable performance and good phenotypic value of different soybean variety traits in different ecological regions were beneficial to the breeding and genetic improvement of soybean varieties.